Fast, accurate, and reliable detection of damage in aircraft composites by advanced synergistic infrared thermography and phased array techniques - Padiyar M, Janardhan; Fragonara, Luca Zanotti; Petrunin, Ivan; Raposo, João; Tsourdos, Antonios; Gray, Iain; Farmaki, Spyridoyla; Exarchos, Dimitrios; Matikas, Theodore E.; Dassios, Konstantinos G. (MDPI, 2021)
This paper presents an advanced methodology for the detection of damage in aircraft composite materials based on the sensor fusion of two image-based non-destructive evaluation techniques. Both of the techniques, phased-array ultrasonics and infra-red thermography, are benchmarked on an aircraft-grade painted composite material skin panel with stringers. The sensors systems for carrying out the inspections have been developed and miniaturized for being integrated on a vortex-robotic platform inspector, in the framework of a larger research initiative, the Horizon-2020 ‘CompInnova’ project.
Keywords: infrared thermography; IRT; automated inspection; phased array ultrasonic testing; NDT; aircraft composites inspection